Healthy and Sustainable Food Shopping: A Survey of Intentions and Motivations - Blanke, Julia; Billieux, Joël; Vögele, Claus (Frontiers in Nutrition, 2022)
Objectives To determine the relationship between sustainable and healthy food shopping behavior comparing general motivation with the immediate intention to act. Method We conducted an online survey of 144 staff at the Cork Institute of Technology, Ireland, using a questionnaire based on the Theory of Planned Behavior and the Self-Determination Theory to compute the Behavioral Intention score and the Relative Autonomy Index in relation to healthy and sustainable grocery shopping. Results The intention to shop healthy food was higher (p < 0.001, Cohen's d = 0.56) than the intention to shop in a sustainable way. A significant intention-action gap was observed for both healthy (p < 0.001, Cohen's d = 0.97) and sustainable grocery shopping (p < 0.001, Cohen's d = 1.78). While there was a significant correlation (p < 0.001) between the longer-term motivations to act in a healthy and sustainable way, this association was not significant (p = 0.16) for the more short-term Behavioral Intention scores. Conclusion and Implications Health was identified as a more important driver for dietary behavior compared to sustainability. While longer-term motivation shows a stronger correlation between healthy and sustainable grocery shopping, short-term intentions do not follow this pattern as strongly. A significant intention-action gap exists for both, which is stronger for sustainability than for health.